Racial differences and an increased systemic inflammatory response are seen in patients with COVID-19 and ischemic stroke (2020)
Objective To describe the difference in clinical presentation, including race, of ischemic stroke between patients with and without novel coronavirus disease 2019 (COVID-19), and the association of inflammatory response with stroke severity. Methods This is a retrospective, observational, cross-sectional study of patients (n ​= ​60) admitted with ischemic stroke between late March and early May 2020. All patients were tested for COVID-19 during admission. Demographic, clinical, and laboratory data was collected through electronic medical record review. Descriptive statistics was performed to observe the differences between stroke patients with and without COVID-19 Results 60 hospitalized patients with acute ischemic stroke were included in the analysis. Nine were positive for COVID-19. African-Americans comprised of 55.6% of those that had COVID-19 and stroke and 37.7% of those with only stroke. Stroke patients with COVID-19 had a significantly higher NIHSS [18.4 (8.8)] and neutrophil-to-lymphocyte ratio (NLR) [7.3 (4.2) vs 3.8 (2.8); P ​= ​0.0137] than those without. Those with COVID-19 also had a significantly higher mortality rate (44.4% vs. 7.6%; p ​< ​0.001). Conclusion We observed a cohort of patients, including a large proportion of African-Americans, who developed ischemic stroke with or without COVID-19. An exaggerated inflammatory response, as indicated by NLR, likely plays a role in stroke severity among COVID-19 patients that concurrently develop ischemic stroke.